Trio : a novel - Boyd, William, 1952- (Alfred A. Knopf, 2021)
"From the award-winning, best-selling author comes a rollicking novel with a dark undertow, set around three unforgettable individuals and a doomed movie set. A producer. A novelist. An actress. It's summer 1968--a time of war and assassinations, protests and riots. While the world is reeling, our trio is involved in making a disaster-plagued, Swingin' Sixties British movie in sunny Brighton. All are leading secret lives. As the movie shoot zigs and zags, these layers of secrets become increasingly more untenable. Pressures build inexorably. The FBI and CIA get involved. Someone is going to crack--or maybe they all will. From one of Britain's best loved writers comes an exhilarating, tender novel--by turns hilarious and heartbreaking--that asks the vital questions: What makes life worth living? And what do you do if you find it isn't?"--